Menganalisis Gaya Lorentz dalam Sistem Listrik dan Magnetik - Muhammad Jhoni; Okta Selviana; Juniah Juniah; Silfiah Damayanti (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
This experiment is about the exploration of Lorentz forces in electric and magnetic systems with the aim of understanding the fundamental interactions between electric fields and magnetic fields. The Lorentz force has an important role in electromagnetics and provides a deeper understanding of physical phenomena involving theoretical analysis and experiments involving simple electricity and magnetism. In theoretical analysis, the concepts and basic equations of Lorentz force are explained mathematically. Experiments are carried out using special devices that generate controlled electric and magnetic fields. The results of this experiment show that the Lorentz force affects the movement of charged particles in electric and magnetic fields. In experiments, charged particles exposed to Lorentz Light experience deviations from their expected paths. This confirmed the basic principles of electromagnetism